The effects of exercise interventions on health and fitness of firefighters: A meta‐analysis. (10th March 2019) - Andrews, Katie L.; Gallagher, Stephen; Herring, Matthew P.
Abstract : Objective: The present review synthesized the available empirical evidence to provide support of the effectiveness and feasibility of exercise interventions for improving health and fitness of firefighters. Methods: Nine randomized controlled trials (RCTs) published before May 2018 were located using Google Scholar, MEDLINE, PsycINFO, PubMed, and Web of Science. RCTs involved 462 (18 Females) active‐duty firefighters, an exercise intervention, and reported changes in health and/or fitness. Hedges' d effect sizes quantified the magnitude of the effects of exercise compared to control conditions. Aggregated mean effects for differential modes of exercise (aerobic exercise training (AET), resistance exercise training (RET), or combined (AET + RET)) were also calculated. Random effects models were used for all analyses. Results: Exercise significantly improved body fat percentage (Δ = 0.52, [95% CI: 0.16‐0.88] z = 2.81, P = 0.005, k = 4), aerobic capacity (Δ = 1.20, [0.52‐1.87] z = 3.48, P = 0.000, k = 8), endurance (Δ = 1.74, [0.94‐2.53] z = 4.03, P = 0.000, k = 10), strength (Δ = 1.27, [0.42‐2.11] z = 2.93, P = 0.003, k = 9), and power (Δ = 1.02, [0.52‐1.52] z = 4.00, P = 0.000, k = 2). Specifically, RET improved body fat percentage (Δ = 0.87, [0.38‐1.36] z = 3.47, P = 0.000, k = 2), aerobic capacity (Δ = 3.06, [2.37‐3.75] z = 8.65, P = 0.000, k = 2), endurance (Δ = 2.79, [1.48‐4.09] z = 4.19, P = 0.000, k = 6), strength (Δ = 1.44, [0.49‐2.39] z = 2.97, P = 0.002, k = 8), and power (Δ = 1.02, [0.52‐1.52] z = 3.99, P = 0.000, k = 2), while AET improved aerobic capacity (Δ = 0.69, [0.24‐1.15] z = 3.01, P = 0.000, k = 3), and AET + RET improved aerobic capacity (Δ = 0.52, [0.15‐0.89] z = 2.78, P = 0.005, k = 3) and endurance (Δ = 0.44, [0.19‐0.70] z = 3.41, P = 0.000, k = 3). Conclusions: The present results provide evidence of the positive effects of exercise interventions, particularly RET, to improve outcomes of health and fitness associated with superior job performance and reduced risk of injury and CVD.